Manhaj dan aqidah ahlussunnah wal jamaah menurut pemahaman ulama salaf Muhammad Abdul Hadi Al Mishri; penerjemah, As ad Yasin, Abu Fahmi, Ibnu Majah; penyunting, M. Solihat - ABDUL HADI AL MISHRI, Muhammad; Yasin, As ad; Abu Fahmi; Marjan, Ibnu; Solihat, M (Gema Insani Press, 1994)
182 hlm 21 cm